Ideologi Islam-Jawa pada Kumpulan Puisi Mantra Orang Jawa Karya Sapardi Djoko Damono - Heri Isnaini (Balai Bahasa Provinsi Riau, 2018)
This article describes the Islam-Javanese ideology in Sapardi Djoko Damono’s Mantra Orang Jawa poetry collection. The depiction of the ideology is examined based on the concept of signs that appear in it. Those signs are then analyzed based on the Pierce’s semiotics theory by regarding representament, object, and interpretant. Further, this article shows the relationship of those signs with other text. The discussions led to the meaning of the concept of IslamJavanese ideology represented in Sapardi Djoko Damono’s Mantra Orang Jawa poetry collection. Finally, this article also offers a reconstruction of the Islam-Javanese society’s classification which tends to be aristocratic. Thus, the Islam-Javanese societies classification proposed by Clifford Geertz, namely santri, priayi, and abangan should be enhanced with the ideology of Islam-Javanese which tends to avoid sharia centric as part of normative Islam.